Clinical and Sociodemographic Characteristics Associated with Emergency Peripartum Hysterectomy due to Puerperal Sepsis in Malawi - Mary Stokes; Amber Olson; Clare Algeo; Bakari Rajab; Carolyn Mwalwanda; Deepa Dongarwar; Rachel Pope (Global Health and Education Projects, Inc., 2022)
Background and Objective: In Malawi, emergency peripartum hysterectomy continues to be routine for the management of puerperal sepsis. While the hysterectomy may be life-saving for the mother, it carries with it life-altering permanent sterility. The surgeon is left with a difficult dilemma: remove the infection source (uterus) to preserve the life of the patient at the cost of her fertility, or preserve the uterus and fertility but risk worsening infection and possible death for the patient. The objective of this study was to (1) identify characteristics associated with mortality post-laparotomy due to puerperal sepsis and (2) identify characteristics associated with emergency peripartum hysterectomy in the management of puerperal sepsis. Methods: In this retrospective chart review, we obtained medical records of patients who underwent laparotomy secondary to puerperal sepsis at a tertiary hospital in Lilongwe, Malawi. Data collected included demographic information and clinical findings. These data were compared between women with and without adverse outcomes. Chi-squared tests were used to determine if there were significant relationships between variables and outcomes. Results: Fifty-eight patient records met inclusion criteria. The following characteristics were significantly associated with mortality: age greater than 30, multiparity, vaginal delivery, and intensive care unit admission. Cesarean delivery and an intraoperative finding of necrosis were significantly associated with hysterectomy. Conclusion and Global Health Implications: Emergency peripartum hysterectomy in the setting of puerperal sepsis is a significant source of maternal morbidity and mortality. To prevent emergency peripartum hysterectomy, it is important to have prompt recognition and treatment of puerperal sepsis, to have access to adequate antibiotics, and to have standards to guide the role of hysterectomy as the definitive and necessary treatment for puerperal sepsis.   Copyright © 2022 Stokes et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.